2006
DOI: 10.1002/jcu.20237
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of holoprosencephaly with ethmocephaly via 3-dimensional sonography

Abstract: We present the prenatal 3-dimensional (3D) sonographic findings in a case of holoprosencephaly with ethmocephaly at 32 weeks' gestation. The sonographic diagnosis was based on the intracranial findings of a single ventricle and bulb-shaped appearance of the thalami and facial abnormalities, including hypotelorism with proboscis. Chromosome study of the fetus revealed a normal female karyotype (46,XX). Postmortem examination confirmed the 3D sonographic findings. This case demonstrates that the use of 3D sonogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In contrast, antenatal ultrasound was favourable in the majority of studies (n=35) for a loss in utero population 42 43 46 56 60 68 78–80 83 84 89 90 93 95 97 99 100 109 114 118 120 125 127 130 135 138 142 150 155 157 161 169 170 173. Only 12 studies favoured autopsy,70–72 96 115 123 126 134 149 154 163 164 and 5 studies presented a 50:50 split between agreement and disagreement 44 132 144 162 171…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In contrast, antenatal ultrasound was favourable in the majority of studies (n=35) for a loss in utero population 42 43 46 56 60 68 78–80 83 84 89 90 93 95 97 99 100 109 114 118 120 125 127 130 135 138 142 150 155 157 161 169 170 173. Only 12 studies favoured autopsy,70–72 96 115 123 126 134 149 154 163 164 and 5 studies presented a 50:50 split between agreement and disagreement 44 132 144 162 171…”
Section: Resultsmentioning
confidence: 95%
“…However this only amounted to 54 studies in total as some artices described different tests from the same study. Of the 134 indirect evidence papers or abstracts, 133 were synthesised41–174 as well as a single trial record 175. None of the seven included trials identified from trial registries reported interim or final results and only four remain active 176–179.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][10][11][12][13][14][15][16][17] Three-dimensional sonographic evaluations of holoprosencephaly and cebocephaly have been described. 13,14,[16][17][18] Only 1 of the referenced case reports, a fetus at 29 weeks' menstrual age with trisomy 13, included a 3D/4-dimensional (4D) image of cebocephaly. 14 Sanz-Cortes and colleagues 13 reported a case of 3D sonographic prenatal diagnosis of lobar holoprosencephaly associated with cebocephaly; however, no images of the fetal face were provided.…”
Section: Discussionmentioning
confidence: 99%